One pot solvent free synthesis and in vitro antitubercular screening of 3-aracylphthalides against mycobacterium tuberculosis - Limaye, Rohan A.; Kumbhar, Virendra B.; Natu, Arun D.; Paradkar, Madhusudan V.; Honmore, Varsha S.; Chauhan, Rubia R.; Gample, Suvarna P.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2013)
One pot synthesis of 3-Aracylphthalide was accomplished in good yield by reacting 2-carboxy benzaldehyde with various aromatic methyl ketones in presence of methane sulphonic acid. Various phthalides thus obtained were characterized with spectral techniques. These phthalides were subjected to in vitro antitubercular screening against Mycobacterium tuberculosis H37Ra (MTB) by using XRMA protocol. Among the phthalides screened, four exhibited half maximal inhibitory concentration (IC50) in the range of 0.81-1.24 mu g/ml thereby providing potential lead compounds for future drug discovery studies. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 3-Aracylphthalide; Antitubercular activity; Methane sulphonic acid; One pot synthesis

Online tools and antiviral databases for the development of drugs against coronaviruses - Aher, Rahul Balasaheb; Sarkar, Dhiman (In Silico Modeling of Drugs Against Coronaviruses: Computational Tools and Protocols, 2021)
The current crisis of coronavirus pandemic has created an urgent need for readily available scientific information to the researchers, students, professionals, and journalists. The scientific information for the research is costly, and most of the universities and research institutes cannot afford to subscribe to all the coronavirus-related journals/articles during this crisis time. In order to expedite the process of vaccine development and discovery of anti-COVID drugs, most of the pharmaceutical companies, research institutes and publishers are playing a key role and working on war footing to get either a vaccine or an anti-COVID drug as early as possible. The collective efforts are required from everyone in this testing time of the corona crisis. To provide our contribution to the scientific community, we have made here an attempt to give an overview of some of the tools and resources freely available that probably provide some insights in data mining and screening of novel lead molecules toward coronavirus. We have collected and compiled the information of open access online tools and antiviral databases essential for the discovery and development of corona vaccine and anti-COVID drugs. The open access tools include Open Educational Resources (OERs), Google cloud, online prediction server, web-based viewer, etc., while the antiviral databases include libraries of synthetic and untested compounds, antiviral drug databases, antiviral peptides, etc. The information presented in this chapter will help the researchers to use them directly in their projects of coronavirus drug discovery.